Kazuo Ishiguro and ethics - Colombino, Laura (New York : Routledge, Taylor & Francis Group, 2025)
"Kazuo Ishiguro and Ethics addresses the philosophical issues that lie at the heart of Ishiguro's fiction, shedding light on the moral condition of his characters - their sense of responsibility and pride in service, their attempts at self-determination, the value they assign to loyalty, love and friendship. Ethics in Ishiguro's work is structured around the tension between the limits of the characters' agency and their striving towards the good. Ishiguro's novels are shown to tackle fundamental questions posed by ancient Greek philosophers, especially Plato, and modern Western ones, from Adam Smith through Jean-Paul Sartre to Martha Nussbaum. What is the human soul? What is dignity? What does it mean to be human? These issues are expressed in his narrative world through the universal and timeless language of myths, allegories and images that are both ancient and modern as well as cross-cultural"--
Introduction : Ishiguro's ethical, existential and emotional worlds -- What is a good life? The Remains of the day as an aporetic dialogue on dignity -- Wounded idealists travel the world : anxiety, responsibility and retribution in the Unconsoled and When we were orphans -- Not at home in the world : longing for the possible and caring for the other in Never let me go -- Ethics, myth and the narrative voice in the Buried giant -- The soul's desire for the good : heliotropic mythology and anamorphic mirrors in Klara and the sun -- Coda : ethics and the arena of conflicting emotions.
Keywords: Ishiguro, Kazuo, -- 1954- -- Criticism and interpretation; Ishiguro, Kazuo, -- 1954- -- Themes, motives; Ethics in literature; English literature -- 20th century -- History and criticism; LITERARY CRITICISM / Science Fiction & Fantasy; PHILOSOPHY / Ethics & Moral Philosophy